The interaction of CO molecules on Au–Rh bimetallic nanoclusters supported on a thin film of Al2O3/NiAl(100). Issue 22 (27th February 2017) - Lee, Hsuan; Liao, Zhen-He; Hsu, Po-Wei; Hung, Ting-Chieh; Wu, Yu-Cheng; Lin, Yuwei; Wang, Jeng-Han; Luo, Meng-Fan
Abstract : The varied infrared absorption intensity of CO on bimetallic clusters reflects altered electronic states of CO-binding surface atoms. Abstract : The interaction of CO molecules adsorbed on Au–Rh bimetallic nanoclusters supported on an ordered thin film of Al2 O3 /NiAl(100) was studied, primarily with infrared reflection absorption spectroscopy and density-functional-theory calculations. The bimetallic clusters, grown by sequential deposition of vapor Au and Rh onto the Al2 O3 /NiAl(100) surface at 300 K, had diameters of 1.2–3.0 nm and heights of 0.4–1.2 nm; they had a fcc phase and grew in the orientation (100). The infrared absorption line for CO adsorbed on Au sites (COAu ) of the bimetallic clusters at 110 K was narrow (centered about 2100 cm −1 ) and intense, which results largely from the small adsorption energy and large dipole moment of COAu, whereas that on Rh sites (CORh ) was broad (1880–2100 cm −1 ) and weak, which contrasts also with its counterpart on pure Rh clusters. Upon increasing the temperature to remove COAu, the absorption line for CORh narrowed and the intensity increased; at 300 K, the line width decreased by 30–40% and the absorption intensity was enhanced by 40–60%. The former arose, after the desorption of COAu, from a decreased CO–CO interaction and inhomogeneous broadening; the latter corresponded to an enhanced dipole moment of CORh, attributed to a promoted charge transfer from the CORh -binding Rh to the neighboring Au and consequently increased charge donated from CORh to Rh. The varied IR absorption for adsorbed CO can thus serve as an indicator for the charge transfer between the components in bimetallic clusters.